The Message of I Peter: the way of the cross - Clowney, Edmund P. (Leicester Inter-Varsity, 1994)
The message of 1 Peter The way of the cross. Out of his first-hand knowledge as an apostle of Christ, Peter shows us what the story of Jesus' life means for us as we take up our cross and follow him.
Keywords: Bible. -- Epistles of Peter, 1st -- Commentaries. I Petrus (bijbelboek) Christianity -- Scriptures